PENGEMBANGAN MEDIA PEMBELAJARAN ARTICULATE STORYLINE 3 BERBASIS MODEL PROBLEM BASED LEARNING PADA TOPIK GOTONG ROYONG KELAS IV SEKOLAH DASAR - Selvi; Reinita; Anita, Yesi; Desyandri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
A preliminary study at three elementary schools in District 1 of Lubuk Kilangan revealed that Pancasila education lessons remain insufficiently interactive, and teachers rarely utilize digital media in the learning process. This situation has the potential to dampen students’ enthusiasm and engagement in learning. Therefore, this study aims to develop Articulate Storyline 3-based learning media using the Problem-Based Learning model for the fourth-grade elementary school curriculum on the topic of gotong royong that meets the criteria of validity, practicality, and effectiveness. This study employs a Research and Development (R&D) approach using the ADDIE model, which comprises five stages: analysis, design, development, implementation, and evaluation. The research subjects include subject matter experts, fourth-grade teachers, and fourth-grade students from three elementary schools in District 1 of Lubuk Kilangan. Research instruments include a validation sheet, a practicality questionnaire, and learning outcome evaluation questions. The results of the study indicate that the developed learning media falls into the “highly valid” category with an average of 95.3%, comprising subject matter expert validation at 94%, language expert validation at 98%, and media expert validation at 94%. The practicality test yielded an average score of 85.33%, falling into the “highly practical” category, which included teacher ratings of 85.33% and student ratings of 91.23%. In addition, this medium has proven effective in improving student learning outcomes on the topic of reciprocal cooperation. Based on these findings, it can be concluded that Articulate Storyline 3-based learning media is suitable for use as an innovative alternative in teaching Civic Education to fourth-grade elementary school students.